Islamic Eco-Sufism in the Ganti Langse Ritual Tradition at Alas Ketonggo Srigati Ngawi, Indonesia - Niken Dyah Hayu Pratiwi; Titis Srimuda Pitana; Wakit Abdullah Rais (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study examines the implementation of Islamic eco-Sufism within the ganti langse ritual tradition at Alas Ketonggo Srigati, Ngawi Regency. The research aims to explore the integration of Islamic spiritual values, local wisdom, and ecological awareness embodied in the ritual practices of the local community. This study employed a qualitative descriptive method with an eco-Sufism approach. Data were collected through observation, interviews, documentation, and literature review involving juru kunci, local community members, and pilgrims. The findings reveal that the ganti langse ritual is not merely a hereditary cultural ceremony but also represents a spiritual and ecological practice that emphasizes harmony between humans, nature, and God. The ritual reflects eco-Sufistic values through environmental preservation, sacred respect for nature, and the cultivation of spiritual awareness. Philosophical concepts such as memayu hayuning bawana demonstrate the community’s commitment to maintaining cosmic balance and environmental sustainability. Furthermore, the ritual integrates Islamic teachings through prayers, spiritual purification, and moral responsibility toward nature. The study concludes that the ganti langse ritual functions as a medium for cultivating ecological ethics and collective environmental consciousness rooted in Islamic spirituality and Javanese local wisdom. Therefore, this tradition remains highly relevant in responding to contemporary environmental crises and strengthening religious-based ecological awareness in society